GABAA α subunit control of hyperactive behavior in developing zebrafish. Issue 4 (2nd February 2022) - Barnaby, Wayne; Dorman Barclay, Hanna E; Nagarkar, Akanksha; Perkins, Matthew; Teicher, Gregory; Trapani, Josef G; Downes, Gerald B
Abstract: GABAA receptors mediate rapid responses to the neurotransmitter gamma-aminobutyric acid and are robust regulators of the brain and spinal cord neural networks that control locomotor behaviors, such as walking and swimming. In developing zebrafish, gross pharmacological blockade of these receptors causes hyperactive swimming, which is also a feature of many zebrafish epilepsy models. Although GABAA receptors are important to control locomotor behavior, the large number of subunits and homeostatic compensatory mechanisms have challenged efforts to determine subunit-selective roles. To address this issue, we mutated each of the 8 zebrafish GABAA α subunit genes individually and in pairs using a CRISPR-Cas9 somatic inactivation approach and, then, we examined the swimming behavior of the mutants at 2 developmental stages, 48 and 96 h postfertilization. We found that disrupting the expression of specific pairs of subunits resulted in different abnormalities in swimming behavior at 48 h postfertilization. Mutation of α4 and α5 selectively resulted in longer duration swimming episodes, mutations in α3 and α4 selectively caused excess, large-amplitude body flexions (C-bends), and mutation of α3 and α5 resulted in increases in both of these measures of hyperactivity. At 96 h postfertilization, hyperactive phenotypes were nearly absent, suggesting that homeostatic compensation was able to overcome the disruption of even multiple subunits. Taken together, our results identify subunit-selective roles for GABAA α3, α4, and α5 in regulating locomotion. Given that these subunits exhibit spatially restricted expression patterns, these results provide a foundation to identify neurons and GABAergic networks that control discrete aspects of locomotor behavior.